2013
DOI: 10.1517/17530059.2013.763795
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil gelatinase-associated lipocalin as diagnostic and prognostic tool for cardiovascular disease and heart failure

Abstract: The authors believe that NGAL should be used as a clinical diagnostic tool to predict outcomes in patients with CVD. Growing evidence has illustrated the biological role that neutrophils, such as NGAL, play in inflammation and atherosclerosis. Further studies are needed to determine NGAL's stability in serum and urine, and to substantiate its widespread use, but there are expanding possibilities for this biomarker in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 84 publications
0
12
0
1
Order By: Relevance
“…LCN2 has been implicated in several critical biological processes, including innate immunity, cell proliferation, and apoptosis. Serum and urine LCN2 are considered as biomarkers for early diagnosis of acute kidney injury (Haase-Fielitz et al 2014; Makris and Kafkas 2012) and cardiovascular disease (Iqbal et al 2013). As Lcn2 was significantly induced by silica, bleomycin, or paraquat from the microarray analysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…LCN2 has been implicated in several critical biological processes, including innate immunity, cell proliferation, and apoptosis. Serum and urine LCN2 are considered as biomarkers for early diagnosis of acute kidney injury (Haase-Fielitz et al 2014; Makris and Kafkas 2012) and cardiovascular disease (Iqbal et al 2013). As Lcn2 was significantly induced by silica, bleomycin, or paraquat from the microarray analysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical studies have confirmed the diagnostic and prognostic value of NGAL in various settings, 6 , 8 but few of them used the RT-POCT NGAL in critically ill patients in the ED for evaluating its efficacy. In this study, we reported our experience of RT-POCT NGAL for detecting AKI in critically ill patients of an urban university tertiary hospital ED.…”
Section: Introductionmentioning
confidence: 99%
“…14 Circulating NGAL is under intense investigation as a diagnostic and prognostic tool for cardiovascular diseases. 15 High plasma NGAL predicts all cause mortality and major adverse cardiovascular events in ST segment elevation myocardial infarction, 16 as well as in the general population. 17,18 In patients with coronary artery disease, levels of circulating NGAL reflect the degree of inflammatory process.…”
Section: Introductionmentioning
confidence: 99%